2022
DOI: 10.32598/immunoregulation.4.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Routine Laboratory Parameters as a Tool for Predicting Death in Patients With COVID-19

Abstract: Background: The complexity of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) makes the clinical course of the disease develop rapidly, causing severe and deadly complications. Identifying effective laboratory biomarkers able to predicting patients based on their risk. This study aimed to look for those serobiomarkers in hospitalized patients with Coronavirus Disease 2019 (COVID‐19). Materials and Methods: In this retrospective observational study, 114 patients with COVID-19, admitted to Valia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Notably, a higher mortality rate of COVID-19 has been reported in end-stage renal disease and kidney transplant patient recipients. Recent literature describes SARS-CoV-2 infections in diabetes and DKD; for detailed review, see [ 7 , 9 ]. These medical literature points out that patients with both pathologies (DKD and COVID-19) develop multiple pathophysiological mechanisms between the lung and kidney organs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a higher mortality rate of COVID-19 has been reported in end-stage renal disease and kidney transplant patient recipients. Recent literature describes SARS-CoV-2 infections in diabetes and DKD; for detailed review, see [ 7 , 9 ]. These medical literature points out that patients with both pathologies (DKD and COVID-19) develop multiple pathophysiological mechanisms between the lung and kidney organs.…”
Section: Introductionmentioning
confidence: 99%
“…for detailed review [23,25]. This medical literature points out that patients with both pathologies (DKD and COVID- 19) develop multiple pathophysiological mechanisms between the lung and kidney organs.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, since the beginning of the COVID-19 pandemic, it has been observed that those comorbidities, including the development of diabetes chronic kidney disruptions, are associated with severe symptoms in patients with SARs-CoV-2 variants [21-24]. There are recent literature describing SARS-CoV-2 infections in diabetes and DKD; for detailed review [23,25]. This medical literature points out that patients with both pathologies (DKD and COVID-19) develop multiple pathophysiological mechanisms between the lung and kidney organs.…”
Section: Introductionmentioning
confidence: 99%